Relation of atrophic gastritis with Helicobacter pylori-CagA+ and interleukin-1 polymorphisms - Sierra Ramos, Rafaela (2008)
Artículo científico -- Universidad de Costa Rica. Instituto de Investigaciones en Salud, 2008